1988
DOI: 10.1037/0012-1649.24.6.776
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and posing of emotional expressions by abused children and their mothers.

Abstract: Twenty abused and 20 nonabused pairs of children (3 to 7 years of age) and their mothers participated in a facial expression posing task and a facial expression recognition task. The expressions produced by subjects were judged on emotion content by naive raters and were coded using Friesen and Ekman's (1984) Emotion Facial Action Coding System (EMFACS). Data analysis indicated that abused children and their mothers pose less recognizable expressions than nonabused children and mothers. Although abused childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
112
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(122 citation statements)
references
References 25 publications
8
112
1
1
Order By: Relevance
“…Consistent with prior reports (e.g., Camras et al, 1988), the present study suggests potentially important differences in the communication of emotion by physically abusive and nonmaltreating mothers. Physically abused children demonstrated an enhanced perceptual preference for expressions of anger, leading one to expect that maltreating mothers would be better at anger production.…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with prior reports (e.g., Camras et al, 1988), the present study suggests potentially important differences in the communication of emotion by physically abusive and nonmaltreating mothers. Physically abused children demonstrated an enhanced perceptual preference for expressions of anger, leading one to expect that maltreating mothers would be better at anger production.…”
Section: Discussionsupporting
confidence: 82%
“…Maltreated children demonstrate deficits in their ability to pose emotion expressions, as do their mothers in some studies (Camras et al, 1988;During & McMahon, 1991). Maltreated children also are more inhibited in their emotion expression (i.e., less expression) during conflict situations compared to nonmaltreated peers (Camras & Rappaport, 1993).…”
Section: Emotion Expression: Psychopathological Populationsmentioning
confidence: 99%
“…Extant work indicates that some deficits exist in the emotion understanding of children at-risk for psychological disorder. For example, abused and maltreated children exhibit deficits in the recognition of face expressions of emotion (e.g., Camras, Grow, & Ribordy, 1983;Camras & Rappaport, 1993;Camras et al, 1990;Camras et al, 1988). Maltreated children, children at risk for disruptive behavior disorders, and ''hardto-manage'' preschoolers demonstrated poorly developed understandings of the causes of emotion, for example, by providing fewer appropriate examples of triggers or cues for emotion (e.g., Camras, Sachs-Alter, & Ribordy, 1996;Cook, Greenberg, & Kusche, 1994;Greenberg et al, 1995;Rogosch, Cicchetti, & Aber, 1995;Shipman & Zeman, 1999).…”
Section: Emotion Understanding: Psychopathological Populationsmentioning
confidence: 99%
“…Several studies [Disbrow et al, 1977;Frodi and Lamb, 1980;Kropp and Haynes, 1987;Pruitt, 1983] have shown that abusive and high-risk parents exhibit less ability to discriminate among emotions than comparison groups. However, other studies [Balge and Milner, 2000;Camras et al, 1988;During and McMahon, 1991] failed to find differences among groups. The mixed findings may be due to the fact that emotion recognition differences between abusive and nonabusive mothers are modest [Camras et al, 1988] and/or are moderated by the type of stimuli used [Balge and Milner, 2000;Camras et al, 1988].…”
Section: Child Physical Abuse Empathy and Attributional Biasmentioning
confidence: 84%
“…However, other studies [Balge and Milner, 2000;Camras et al, 1988;During and McMahon, 1991] failed to find differences among groups. The mixed findings may be due to the fact that emotion recognition differences between abusive and nonabusive mothers are modest [Camras et al, 1988] and/or are moderated by the type of stimuli used [Balge and Milner, 2000;Camras et al, 1988].…”
Section: Child Physical Abuse Empathy and Attributional Biasmentioning
confidence: 84%